Nursing diagnoses from NANDA's taxonomy in women with a hospitalized preterm child and King's conceptual system (Revista Latino-Americana de Enfermagem, 2000)
This study aimed at identifying nursing diagnoses presented by mothers with a hospitalized preterm child in an NICU by the use of King's Conceptual System and Taxonomy I of NANDA's nursing diagnoses. The case-study methodology was applied to 35 puerperal women. Eight diagnoses were identified, the frequency of which was over 50%, as follows: Risk of Infection, Risk of Injury, Impaired Tissue Integrity, Altered Health Maintenance, Risk of Inefficient Breast-feeding; Risk of Altered Parent/Infant Attachment; Fear; Parental Role Conflict and Impaired Social Interaction.